Quality of Glycine max (soybean) and Helianthus annuus (sunflower) oils stored in different environments and their suitability for consumption (Research, Society and Development, 2023)
Soybean and sunflower oils contribute to the diet in many countries, serving as a source of protein, lipids and fatty acids, and repair worn-out tissues and are a useful source of energy. Their excessive or inadequate consumption may provide increased risk of developing various diseases. Sunflower seed provides 20-40% of oil and soybeans provide oil with immense advantages due to their high content of essential fatty acids. This work aimed to evaluate the physicochemical quality of soybean and sunflower oils and their effects on health. 5 samples of oils: A, sealed sunflower oil exposed to ambient light; B, sealed sunflower oil without exposure to sunlight; C, sealed soybean oil exposed to ambient light; D, unsealed sunflower oil exposed to ambient light and E, sealed soybean oil without exposure to light were evaluated by determining the acidity index, through titration with NaOH 0. 1N, peroxide index, by titration with Na2S2O3 0.01N, moisture, by dissection at 105ºC, rancidity, by qualitative method and vitamin A by iCheck Chroma. The NM 425:2012 legislation was used to verify the suitability or otherwise of the samples. Moisture ranged from 0.1 to 0.92 w/w, acidity index from 0.17 to 0.34mgKOH, peroxide index from 4 to 15.2 meq.O2/Kg, vitamin A between 13.27 and 29.95mgRe/Kg and positive rancidity. The results showed that the acidity index and vitamin A provided adequacy and the other parameters showed inadequacy for consumption.